Probiotic Characteristics of Streptococcus thermophilus and Lactobacillus bulgaricus as Influenced by New Food Sources - Ashly Castro; Ricardo S. Aleman; Miguel Tabora; Shirin Kazemzadeh; Leyla K. Pournaki; Roberto Cedillos; Jhunior Marcia; Kayanush Aryana (Microorganisms, 2023)
The current research aimed to evaluate the potential effects of Solanum mammosum, Dioon mejiae, and Amanita caesarea on Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus survival and performance after exposure to different harsh conditions such as bile, acid, gastric juice, and lysozyme to mimic the digestive system from mouth to the intestine. Probiotic protease activity was observed to evaluate the proteolytic system. Probiotics were cultured in a broth mixed with plant material, and after incubation, the results were compared to the control sample. Therefore, plant material’s total phenolic compound, total carotenoid compound, antioxidant activity, sugar profile, and acid profile were obtained to discuss their impact on the survival of probiotics. The results indicate that Amanita caesarea negatively affected probiotic survival in the bile tolerance test and positively affected Lactobacillus bulgaricus in the protease activity test. Otherwise, the other plant material did not change the results significantly (p > 0.05) compared to the control in different tests. Consequently, Solanum mammosum and Dioon mejiae had no significant effects (p > 0.05) in increasing probiotic survival.